Economic Burden of Diabetes In India: A Review (Journal of Pharmaceutical Negative Results, 2022)
Diabetes imposes a significant impact on health systems and societies. Both direct and indirect expenditures contribute to the cost of diabetes mellitus. The direct cost of diabetes is based on a variety of expenses linked to treatment, delivery of therapy, laboratory testing, and investigations, as well as travel, lodging, and other incidentals. For indirect expenses, information about present employment, illness-related job changes, issues at existing employment, changes in ability to do work, and absenteeism. Diabetes has multiple financial ramifications for society, including direct expenses for those with the disease, their families, and the health care industry, indirect expenses for society and the government that affect productivity, and intangible expenses that have a negative impact on quality of life. Very little is known about the financial toll diabetes has on the developing world, adetailed review of which is the aim of this article.